Non-invasive vagus nerve stimulation is associated with the reduction in persistent post-concussion symptoms: an observational study - Ament, Michael; Leonard, Emily; Staats, Peter S.; Ingram, Norianne T. (Frontiers in Neurology, 2025)
IntroductionTraumatic brain injury (TBI) remains a major public health challenge, with mild TBI (mTBI) frequently resulting in persistent cognitive, affective, and somatic symptoms. Non-invasive vagus nerve stimulation (nVNS) has demonstrated potential in reducing neuroinflammation and promoting recovery in preclinical TBI models. This retrospective, observational study assessed the impact of adjunctive nVNS on postconcussive symptoms in routine clinical practice.MethodsWe conducted a single-center observational cohort study consisting of 102 patients with mTBI who received adjunctive nVNS as part of standard care. Symptom severity was measured using the Neurobehavioral Symptom Inventory (NSI) at baseline and approximately 112 days post-treatment initiation. The primary outcome was the change in NSI symptom scores. Secondary analyses explored associations between baseline symptom severity, treatment response, and secondary clinical measures. Safety data were collected throughout the study period.ResultsIn this patient cohort, 16 of 22 NSI symptom domains showed significant improvement after three months of treatment with adjunctive nVNS. The most notable reductions were observed for post-traumatic headache (−0.79 ± 1.19; p = 1.97 × 10−8), difficulty concentrating (−0.59 ± 1.25; p = 1.79 × 10−5), dizziness (−0.47 ± 1.14; p = 7.11 × 10−5), and depression/sadness (−0.47 ± 1.12; p = 9.09 × 10−5). Approximately onethird (34%) of patients met responder criteria (≥30% reduction) for at least half of the assessed symptoms, indicating broad and clinically meaningful symptom relief. The length of the interval between injury and treatment initiation did not significantly influence baseline symptom severity or the magnitude of improvement. No devicerelated adverse events were reported.DiscussionIn a naturalistic clinical setting, adjunctive nVNS was associated with significant reductions in post-concussive symptom severity across cognitive, affective, somatic, and vestibular domains in patients with mTBI. These findings support the use of nVNS as a practical, safe, and effective intervention for persisting symptoms due to mTBI. Further prospective, controlled studies are warranted to validate these observations and elucidate underlying mechanisms.